The role of palliative medicine in ICU bed allocation in COVID-19: a joint position statement of the Singapore Hospice Council and the Chapter of Palliative Medicine Physicians - Krishna, LKR (Springer Science and Business Media LLC, 2021)
10.1007/s41649-020-00128-0